Analysis of Innate and Adaptive Immunological Characteristics in Patients with IgG4-Related Disease - Sohn, Kyoung-Hee (Int Arch Allergy Immunol, 2020)
BACKGROUND: Immunoglobulin G4-related disease (IgG4-RD) is a systemic immunological disorder characterized by fibro-inflammatory conditions; however, the pathobiology of IgG4-RD has not been fully identified. OBJECTIVE: This study aimed to analyze systemic differences of innate and adaptive immune cells from healthy controls and patients with IgG4-RD. METHODS: Healthy controls (n = 9) and IgG4-RD patients (n = 7) were recruited with informed consent. Peripheral blood was collected from healthy controls and IgG4-RD patients, and three blood samples from IgG4-RD patients were re-collected two months after the last rituximab (RTX) treatment. The various immune cells and cytokine productions were measured by flow cytometry. RESULTS: Blood CD14+ monocytes and steady-state follicular helper T cells were increased in patients with IgG4-RD. However, there were no changes in other immune cell populations, including B cells, CD4 T cells, CD8 T cells, and innate lymphoid cells. Also, the TGF-β-producing CD14+ monocytes were significantly augmented in patients with IgG4-RD. Two months after RTX treatment, total B cells (CD19+) were depleted; however, the expressions of TGF-β from CD14+ monocytes remained unchanged. CONCLUSION: These findings showed that IgG4-RD is related to the increment of CD14+ monocytes. Besides, controlling increased TGF-β-producing CD14+ monocytes with RTX treatment might be a conducive way to regulate IgG4-RD.